“Help ASD’s with fun way”: detective looking Chart- Plutchik emotion games for kids through VARK model to ASD children - Hassan, Muhamad Hafiz; Wardi, Rainal Hidayat; Mohd Razali, Noraziah; Hishamuddin, Nurul Amy Azura; Ahmad, Muhammad Fakhruddin; Mat Nashir @ Mohd Nasir, Roziani (Academica Press Solutions, 2023)
One of the 17 SDG Sustainable Development Goals announced by the UN in September 2015 is quality education. "Ensure inclusive and equitable quality education and promote opportunities for lifelong learning for all" is the focus of SDG criteria number 4. To ensure that children with special needs, such as Autism Spectrum Disorder (ASD), receive parallel schooling in both their academic and personality components, "Parallel Education." As a complex developmental impairment, autism has no racial, ethnic, or social differences regardless of family income, way of life, or degree of education. Children with autism also have difficulty using their social imagination. In order to better meet their demands for enhancing brain development, the approach in the education sector must identify initiatives in developing teaching and learning resources and tools. For teachers and schools, ministries, communities, parents, guidance (the instructors), and the nation to approach the needs of children, tools for this type of group are required. The disease has a significant impact on three key areas: conduct, social skills, and communication abilities. Additionally, this innovation can be related to behavioural and developmental therapies for ASD in shaping learning that influences parts of cognition and emotion. This game was developed as a teaching tool for autistic kids and serves as a platform to gauge their emotional states using the Plutchik wheel of emotions. The research needs of autistic children in obtaining instruction using the VARK (visual, auditory, reading/writing, and kinesthetic) model informed the development of this game. This study has created a gameboard to raise the emotional level of autistic children through the cognitive and affective domains, ensuring that their particular sensory needs are met in addition to aiding their psychomotor development. By concentrating on emotional evaluation, the study will also uncover new concerns and requirements for autistic kids who have sensory issues. To assist them in learning, educational items (teaching and learning aids) are created in order to help this target group at any canter of autism.